Story of a girl : a novel - Zarr, Sara (Little, Brown and Company, 2017)
In the three years since her father caught her in the back seat of a car with an older boy, sixteen-year-old Deanna's life at home and school has been a nightmare, but while dreaming of escaping with her brother and his family, she discovers the power of forgiveness.